Understanding educators' and learners' perceptions and experiences of their participation in Science Fairs/Expos : a South African case study. - Kahenge, Wendelina Nambahu (Rhodes University, Faculty of Education, Department of Education, 2014)
The rationale behind Science Expos is to develop and empower learners to be able to identify problems and find solutions (Eskom Expo Project Guide Book, 2013). It is believed that involvement in Science Expos arouses learners' interest to pursue science related careers. But despite these ideals, there is still poor participation in Science Expos by educators and learners. I conducted this case study in five schools in Grahamstown, Eastern Cape, South Africa. The purpose of this study was to understand educators' and learners' perceptions and experiences of their participation in Science Expos. The case study was designed within an interpretive paradigm. The data were generated, triangulated and validated by a variety of methods, namely, document analysis, interviews (semi-structured and focus group) and observations. The main findings of the study were that learners who participate in Science Expos attend workshops organised by Scifest and SAEON office with the help of some of the educators and lecturers from Rhodes University. Learners' participation was influenced and assisted by the educators and peers with whom they were able to communicate and share their projects with. It emerged from the study that, as a result of participating in Science Expos, educators (teachers) and learners were exposed to a wide variety of scientific investigations and skills that are necessary for their classroom based-scientific investigations. It also emerged from this study that educators and learners face the challenge of a lack of motivation; insufficient support from schools and parents; time constraints to support learners in their participation and a lack of knowledge among some educators on their learners' projects. Some learners are even discouraged from participating in Science Expos by their peers on the grounds that they have no chance of winning. Teachers therefore require continuous mentorship and capacity building in order to encourage their learners to partake.
Keywords: Science fairs -- South Africa -- Grahamstown; Science -- Study and teaching -- South Africa -- Grahamstown; Vocational guidance -- South Africa -- Grahamstown; School children -- South Africa -- Attitudes; Teachers -- South Africa -- Attitudes; Teacher effectiveness -- South Africa -- Grahamstown